2000
DOI: 10.1046/j.1440-1827.2000.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous carcinoma of the breast

Abstract: We report on a rare distinctive variant of infiltrating ductal carcinoma characterized by sebaceous differentiation of tumor cells. The neoplasm was identified in a lumpectomy specimen from a 45-year-old woman with extensive metastatic disease. In addition to conventional in situ and invasive ductal components, approximately half of the tumor cells exhibited a phenotype resembling tumors of the sebaceous skin appendage with coarsely vacuolated cytoplasm and peripherally displaced nuclei. The sebaceous moiety w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 9 publications
8
58
1
1
Order By: Relevance
“…Regarding the potential therapeutic targets in mammary SC, altogether six cases (including three present cases) were ER and PR-positive [3,5,6] and one case was ER-negative/PR-positive [4]. Three cases were hormone receptors-negative, including one of our cases [8,9].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Regarding the potential therapeutic targets in mammary SC, altogether six cases (including three present cases) were ER and PR-positive [3,5,6] and one case was ER-negative/PR-positive [4]. Three cases were hormone receptors-negative, including one of our cases [8,9].…”
Section: Discussionmentioning
confidence: 72%
“…Two reported cases showed metastasis in one regional lymph node [6,8]; three cases had negative lymph nodes [3][4][5]. Follow-up is available in three cases only: one patient was alive with no evidence of disease 24 months after the operation [8]; the second patient had no evidence of disease after ten months [3]; the third patient had skin and bone metastases 132 months after surgery [5]. Follow-up of our cases indicates that mammary SC might be a highgrade malignant neoplasm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1 Both skin appendages and the secretory and ductal apparatus of the mammary gland share a common embryonic ectodermal anlagen. 13 The origin and pathway of the sebaceous metaplasia in mammary carcinomas remain unclear. It is suggested that there is an association between sebaceous gland metaplasia and squamous metaplasia.…”
mentioning
confidence: 99%